Financial Stability, Industrial Conditions and External Pressure on Financial Statement Fraud in Manufacturing Companies - Anisa Rizki Fitriastuti; Martina Khusnul Umami; Rizky Windar Amelia (Islamic Accounting Journal, 2022)
This study to examine financial stability, industrial conditions and external pressures and their effects on financial reports. Financial stability was tested using ACHANGE, industrial conditions were tested using RECEIVABLE, external pressure was tested using Debt to Asset (DTA), and fraudlent financial statments were test using EDAIT. This study uses secondary data quantitative methods. The population in this study are manufacturing companies listed on the IDX. The analysis technique used is multiple regression analysis which shows that financial stability and industrial conditions have a negative effect on financial statement fraud, while external pressure has a positive effect on financial statement fraudKeywords: Financial Statement Fraud, Financial Stability, Industrial Conditions, External Pressure